Dynamic Motion Residuals in Swath Sonar Data: Ironing out the Creases - Hughes Clarke, John E. (The International Hydrographic Review, 2003)
As the component sensors in swath sonar systems have improved, the focus on total system performance has turned increasingly to the remaining imperfections in the system integration. Of particular concern is. that faint but systematic across track ribbing often remains in otherwise high-quality data. Traditional field calibration procedures primarily look for the signature of static systematic error contributions. These procedures (the conventional patch test) only examine a subset of the possible systematic biases in the configuration of an integrated swath sonar system. Other systematic biases can cause dynamic rather than static signatures in the resulting bathymetric data. These dynamic errors can be separated into those that produce errors that vary with periods in the ocean wave spectrum (most commonly referred to as the ‘wobbles’) and those whose period is dictated by the vessel’s long period accelerations (turns and other course changes, obstacle avoidance and speed changes). Herein the theory behind the cause for a number of common wobble sources is examined. For the case of shallow water surveys, where the ping period is short with respect to the typical wave period, the wobble signatures can be easily discerned. The differences in the signatures of each of the wobbles are highlighted allowing rapid classification and thus a means of removal of the underlying systematic bias.